The melting performance blast furnace slags with high alumina content - Zheng H.-Y.; Zhang Y.; Wang Z.; Du J.-L.; Jiang X.; Gao Q.-J.; Shen F.-M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
With a view to understanding the performance of the blast furnace slag with high Al2O3 content, the effects of w(MgO)/w(Al2O3), w(CaO)/w(SiO2), and w(Al2O3) on the melting performance (melting characteristic temperature and melting heat) of the blast furnace slag with high Al2O3 content were investigated by the differential scanning calorimeter (DSC) method. Experimental results indicate that melting end temperature (Tend) for almost all the slags has no obvious change with the increase of w(MgO)/w(Al2O3), w(CaO)/w(SiO2) and w(Al2O3) of the slag will raise Tend of the slag. When (w(MgO)/w(Al2O3), R, and w(Al2O3) are high, the melting onset temperature (Tonset) of the slag increases with the increase of any variables. When w(CaO)/w(SiO2) is low, Tonset of the slag decreases with the increase of w(Al2O3). w(MgO)/w(Al2O3), w(CaO)/w(SiO2), and w(Al2O3) within the scope of this study and all these factors lead to the increase of the slag melting heat.